Analisis Faktor Penghambat Implementasi Alokasi Dana Desa di Desa Perumnas Simalingkar, Pancur Batu, Kabupaten Deli Serdang - Muhammad Iman Kandias Saraan; Sri Suwitri; A.P. Tri Yuniningsih (Universitas Medan Area, 2019)
From this study there are several actors that hamper the implementation of Village Fund Allocation, namely Resources, Disposition of implementers, and social, political and economic conditions, obstacles to the achievement of the implementation of Village Fund Allocation with the aim of this study to find out the obstacles in the implementation of Deli Serdang Regency Regulations Number 256 of 2017 concerning Village Fund Allocation and factors for achieving policy implementation. The research location was carried out in the Perumnas Simliangkar Village, Pancur Batu District, Deli Serdang Regency. The writing design in this study uses descriptive qualitative methods. The data source used is the primary data source using the interactive interview method and secondary data by searching relevant document data regarding the Village Fund Allocation policy. The results of the study explained that the results of the study showed that in achieving the objectives, the implementation of the Village Fund Allocation (ADD) was not optimal. In addition, the aim of improving governance, development and capacity of social institutions has not been carried out optimally. Likewise, the aim of increasing community participation in community cooperation and community empowerment has not been optimal. Some of the factors that influence the implementation of Village Fund Allocation (ADD) are Resources, disposition attitudes, social, economic and political conditions.